Hubungan Kontribusi Orang Tua dengan Karakter Siswa Kelas IV UPT SD Inpres 6/75 Kading Kecamatan Barebbo Kabupaten Bone - Nur Fahira Septi; Rukayah Rukayah; Mujahidah Mujahidah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research is a quantitative research with a correlational approach which aims to determine the relationship between parental contributions and the character of the fourth grade students of UPT SD Inpres 6/75 Kading, Barebbo District, Bone Regency, with 42 students. Data collection is done by using a questionnaire. Data analysis technique with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of the research showed that the contribution of parents had an average of 46.11 and a percentage of 76.90% in the good category and the average character of fourth grade students had an average of 48.5 and a percentage of 80.99% in the category very good. Based on the results of inferential statistical analysis, the tcount value (2.87) is greater (>) the ttable value (1.68385) at a significance level of 5%. Thus H0 is rejected and H1 is accepted. The results of the study can be concluded that there is a significant relationship between the Contribution of Parents and the Character of Class IV Students at UPT SD Inpres 6/75 Kading, Barebbo District, Bone Regency.